Analisis Pengaruh Kompensasi, Lingkungan Kerja Terhadap Kepuasan Kerja Dan Kinerja Pegawai - Wakerkwa, Nus (JURNAL RISET BISNIS DAN MANAJEMEN, 2017)
This study attempts to to analyze the influence of compensation, work environment to satisfaction work in public and government empowerment their kabupaten the top papua province, then analyze the influence of compensation, work environment of the performance of employees in the community empowerment office and governance their kabupaten the top papua province, next to analyze the influence of satisfaction work of the performance of employees in the community empowerment office and governance their kabupaten the top papua province. This research found that compensation having influence not significantly to the satisfaction of working, working environment have a positive influence significantly to the satisfaction of working, compensation having influence not significantly to the employee performance, working environment have a positive influence significantly to the employee performance, satisfaction of work have a positive influence significantly to the employee performance in office and community empowerment kampung district government peak papua province.Keywords: Compensation, work environment, satisfaction work, performance employees, Papua Province